Homer1 gene products orchestrate Ca2+-permeable AMPA receptor distribution and LTP expression - Rozov, Andrei; Živković, Aleksandar; Schwarz, Martin K. (Frontiers in synaptic neuroscience, 2012)
We studied the role of Homer1 gene products on the presence of synaptic Ca2+-permeable AMPA receptors (AMPARs) and LTP generation in hippocampal CA1 pyramidal neurons, using mice that either lacked all Homer1 isoforms (Homer1 KO) or overexpressed the immediate early gene product Homer1a (H1aTG). We found that Homer1 KO caused a significant redistribution of the AMPARs containing subunit GluA2 from the dendritic compartment to the soma. Furthermore, deletion of Homer 1 enhanced the AMPAR-mediated component of glutamatergic currents at Schaffer collateral synapses. The AMPA/NMDA current ratios were significantly larger in Homer1 KO neurons than in wild-type (WT) neurons. Meanwhile, LTP generation appeared to be unaffected. Conversely, sustained overexpression of Homer1a strongly reduced AMPA/NMDA current ratios and polyamine sensitivity of synaptic AMPARs, indicating that the proportion of synaptic GluA2-containing AMPARs increased relative to WT. LTP maintenance was abolished in H1aTG. Notably, overexpression of Homer1a in Homer1 KO or GluA2 KO mice did not affect LTP expression, suggesting activity-dependent interaction between Homer1a and long Homer1 isoforms with GluA2 containing AMPARs. Thus, Homer1a is essential for the activity-dependent regulation of excitatory synaptic transmission.